Analisis Penerapan RME Pada Unit Coding Rawat Jalan RSUD K.R.M.T Wongsonegoro Semarang - Amaliya Nikmatul Rohmah; Ida Nurmawati; Indah Muflihatin; Syaifuddin Syaifuddin (Politeknik Negeri Jember, 2020)
RSUD K.R.M.T Wongsonegoro Semarang City is one of the hospitals that have implemented an electronic medical record at the end of December 2017. Information systems that support management and service to patients are electronic medical records, especially in outpatient coding units. One factor that plays an important role in the successful application and use of information technology is the user factor. The level of user readiness to accept information technology has a major influence in determining the success or failure of the application of the technology. The purpose of this study was to evaluate the application of electronic medical records in outpatient coding units based on the Technology Acceptance Model (TAM) method. This type of research is qualitative research with the data collection methods, namely interviews, observation and documentation. The subjects of this study were outpatient coding officers. The results showed that based on the aspects of usefulness in the use of electronic medical records in outpatient coding units be very beneficial for officers. Based on the aspect of ease in showing the acceptance of electronic medical records, it is considered easy to understand, flexible enough with the work of officers and easy to used to assist with work. Based on the aspect of interest, it is obtained that outpatient coding officers also show their interest in the system, and plan to use the system in the future, although there are some obstacles. The solution obtained from the problem is making guidelines for the use of electronic medical records, adding electronic signature features to electronic medical records for patient medical resume forms, striving for electricity and electricity networks to remain stable, making updates or updating electronic medical records.